Engaging Spaces How to increase social awareness and human wellbeing through experience design - Camocini, Barbara; Dominoni, Annalisa (Design International, 2022)
The book presents different perspectives of analysis and new models of experience, reconfirming the importance assigned to the wellbeing and human-centered approach in the contemporary spatial design disciplinary debate. The focus on "engaging spaces" is due to the increase of participatory experiences in the design strategies supporting designers who want create tailor made environment to feel people more conscious of the great value of social relations. The title of the book anticipates the aim to explore the transformation process which we are living, both in private and in public spaces, underlining the central role of design to define new qualities of connections to live together in relation with the space around us. The volume is divided into two parts described below. The first, "Social design for engaging spaces", explores private and public space case studies introducing new hybrid dimensions through the social engagement in "living communities" and reports participatory design approaches in the transformation processes of shared common spaces, such as schools, intended as incubators of social practices. The second, "Experience design for engaging spaces", describes more in-depth the experience of human beings in relation to physical and emotional aspects of space, focusing on the quality of the built environment that deeply affects people's wellbeing, social interaction, and cohesion, and investigating ephemeral practices and projects to experience design through a conscious sensorial approach. The pandemic and the return to a "post-pandemic new normal" have led us to further reflect on the spatial processes of transformation and hybridization and their shared use in both the private and public spheres, exploring the importance of participatory and engaging strategies in the different phases of the design process with the aim to increase social awareness. Being back to the physical perception of spaces has confirmed the importance of evaluating the project's sensorial aspects with a new awareness. This novel attitude leads to rediscovering the values of measurable space in the constant confrontation with the virtual perspective that triumphed during the pandemic, introducing the "time" factor in the design discipline even with a broader complexity than before.